Systemic inflammatory regulators and preeclampsia: a two-sample bidirectional Mendelian randomization study - Li, Chu; Tian, Yishu; Dougarem, Djouhayna; Sun, Litao; Zhong, Zixing (Frontiers in Genetics, 2024)
Background: Systemic inflammatory regulators have been associated with preeclampsia (PE) during pregnancy, however, there is inconsistent evidence from animal models and observational results.Methods: Using summary data from genome-wide association studies (GWAS), we performed a bidirectional Mendelian Randomization (MR) analysis done over two samples of systemic inflammatory regulators (n = 8,186) and PE (n = 267,242) of European ancestry. As our primary analysis, we used the random effects inverse variance weighted (IVW). Sensitivity and pleiotropy analysis were conducted using MR-Egger, weighted median, MR pleiotropy residual sum and outlier (MR-PRESSO), and Cochran's Q test.The results indicate that there is a correlation between a higher circulating level of tumor necrosis factor-alpha (TNF-α) and interleukin-9 (IL-9) and an increased risk of PE (odds ratio [OR] = 1.32, 95% confidence interval [CI] = 1.09-1.60, p = 0.004; OR = 1.28, 95% CI: 1.02-1.62, p = 0.033, respectively). Conversely, lower levels of stem cell growth factor beta (SCGF-β) (OR = 0.89, 95% CI: 0.80-0.99, p = 0.027) and interleukin-5 (IL-5) (OR = 0.80, 95% CI: 0.65-0.98, p = 0.030) are linked to an increased risk of PE. Macrophage migration inhibitory factor (MIF) is the downstream inflammatory regulator of PE, according to reverse magnetic resonance imaging studies.Our study suggests that SCGF-β, IL-5, IL-9, and TNF-α causally affected PE risk, while PE is causally associated with MIF. Further studies are needed to validate these biomarkers in managing preeclampsia.